Self- management of diabetes mellitus during the Covid-19 pandemic: Recommendations for a resource limited setting (2020)
Background and aims: The COVID-19 pandemic has challenged both institutional and selfmanagement of diabetes. The ongoing social distancing and lock downs have negatively impacted to access to care and self-management. Methods: This is a narrative review of diabetes management in a resource limited setting during the ongoing COVID-19 pandemic. Electronic databases, namely; Pubmed, CINAHL, EMBASE and Google Scholar were searched for literature. Search terms were “corona virus”, “COVID-19”, “diabetes self-care”, “diabetes self-management education”, “DSME”, “diabetes self-management”, “diabetes self-care in low income countries” and “diabetes management in Zimbabwe”. Results: This paper suggests a culturally tailored educational plan on diabetes selfmanagement of diabetes in a limited resource country, Zimbabwe, amid the ongoing COVID19 pandemic. Components of health education comprised general preventive measures, medications, diet, physical activity, self-monitoring of blood glucose, stress management, foot care, smoking and drinking and preventing complications of diabetes mellitus. Conclusions: We have reemphasized the need for self-care, social support and a collaborative, patient-centered approach to care amid the ongoing COVID-19 pandemic.